KOPERASI SETIA BHAKTI WANITA DAN PROMOSI ONLINE SHOPPING E-KOPWAN DI SURABAYA - Susanti, Ririen (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Promotion is the most important part of process introduction of a product or service to the target consumers. The distinctive techniques in a promotion, among others can use some methods such as advertising and non-personal communication. Using these methods must also consider the design of promotional appearances. All these are done in order to get sympathy from consumers when looking at toward those promotions. These observations were performed at the ‘Setia Bhakti Wanita Cooperate Surabaya’ especially placed on the department of E-Kopwan. This department focuses on informational technology (IT) about that cooperate. The main problem was taken from the department is the promotion of online shopping; where ordering of the results of advertising is less effective because the evidence produced is only eleven (11) transactions through E-Kopwan. The observation results from the study of this business practices are expected to help E-Kopwan, members and non-members of FKJU (Communications Network Enterprises Forum) as a supplier in order to become more effective in running their businesses. Where it will also help the government to promote local products derived from UMKM or MSME (Micro, Small and Medium Enterprises) to the public in order to increase revenue in Indonesia.